JUSTIFICATION OF EXPEDIENCY OF THE PRODUCTION FIXED ASSETS REPLACEMENT OF THE BUILDING ORGANIZATION - Фафлей, Олег; Fabryka, Yuriy; Faflei , Oleh (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The approach was proposed to justify the feasibility of fixed assets replacing in construction. The algorithm was developed to determine the rational time to upgrade of the equipment. The algorithm takes into account the cost of new equipment purchasing, maintenance of existing equipment, as well as its liquidation value. The older are the fixed assets, the more money is needed to keep them in good condition. Increasing the age of the equipment leads to increased costs and reduced profits. In the construction industry, despite the growth of investment, there is no sufficient renewal of fixed assets. The purpose of the study is to develop an algorithm and computer model to justify the feasibility of replacing of fixed assets of the construction organization. For a multi-year planning period, a comprehensive equipment replacement decision consists of intermediate solutions - there may be two alternatives for each year: replacing the equipment or continuing to use it. Next year's economic outcome depends on which alternative was chosen in the previous year. The developed algorithm and the corresponding computer model make it possible to find the best options for replacing the equipment for any period based on the cost of new equipment, annual operating costs and liquidation value of the equipment. The advantage of the proposed computer model is that it can be used to plan the replacement of not only those fixed assets that have recently been purchased, but also those that have been in use for some time. For practical use, it is necessary to regularly summarize and update the data on the funds required for the repair and maintenance of specific types of equipment during the year, and the associated loss of profit. The developed computer model could be implemented to plan the replacement of equipment with different terms of its previous operation. It is expedient to use it not only in the construction organizations, but also at the enterprises of other branches where the equipment quickly wears out because of intensive operation, work in the aggressive environment or at harmful influence of atmospheric factors.